Cholinergic Signaling Alters Stress-Induced Sensitization of Hippocampal Contextual Learning - Hersman, Sarah; Hoffman, Ann N.; Hodgins, Liliann; Shieh, Shannon; Lam, Jamie; Parikh, Ashen; Fanselow, Michael S. (Frontiers in Neuroscience, 2019)
Post-traumatic stress disorder (PTSD) has a profound contextual component, and has been demonstrated to alter future contextual learning. However, the mechanism by which a single traumatic event affects subsequent contextual experiences has not been isolated. Acetylcholine (ACh) is an important modulator of hippocampus-dependent learning such as contextual memory strength. Using Stress-Enhanced Fear Learning (SEFL), which models aspects of PTSD in rats, we tested whether muscarinic cholinergic receptors (mAChR) in dorsal hippocampus (DH) are required during trauma for the effect of trauma on subsequent contextual fear learning. We infused scopolamine or vehicle into DH immediately before stress, and tested fear in both the trauma context and a novel context after a mild stressor. The results show that during learning, ACh acting on mAChR within the DH is required for sensitization of future contextual fear learning. However, this effect is selective for contextual learning, as this blockade leaves discrete cue sensitization intact. Rather than simply sensitizing the BLA, as previous studies have suggested, SEFL requires cholinergic signaling in DH for contextual sensitization.